Optimal control for networked control systems with multiple delays and packet dropouts. (12th May 2020) - Lu, Xiao; Zhang, Qiyan; Liang, Xiao; Wang, Haixia; Sheng, Chunyang; Zhang, Zhiguo
This article focuses on the problem of optimal linear quadratic Gaussian control for networked control systems with multiple delays and packet dropouts. The main contributions are twofold. Firstly, based on the introduced maximum principle for linear quadratic Gaussian system with multiple input delays and packet dropouts, a nonhomogeneous relationship between the state and costate is obtained, which is the key technical tool to solve the problem. Secondly, a necessary and sufficient condition for the optimal networked control problem is given in virtue of the coupled Riccati equations, and the explicit expression of the optimal controller is presented. Numerical examples are shown to illustrate the proposed algorithm.